CHANGES IN VALUES AND ITS RELATIONSHIP WITH SUBJECTIVE WELFARE (CASE STUDY OF THREE GENERATIONS IN IRAN) - Tamizifar , Reihaneh; Tamizifar , Mahdi (PEOPLE: International Journal of Social Sciences, 2018)
This study investigated the procedure of the changes in values and welfare in Iran, which was conducted among three generations in Tehran. The key question is "what differences are found in value changes and subjective welfare of different generations of the population under study; and how these differences associated with the occurred social changes in Iran are?” The sample (n=384) consisted of three generations of Tehran residents: the generation who has lived before Revolution), the generation who has lived in the time of Revolution and the war between Iran and Iraq and the generation of after Revolution. Findings indicated that the tendency towards changes and conservativeness is significantly different among the generations. The average tendencies towards values that showed achievement of personal aims are significantly different among generations. There is a relationship between the first generation’s emotional well-being, and the second and third generations’ subjective welfare. However, the tendency towards self-transcendence is of no significant difference among generations and these values are only related to the second generation’s subjective and cognitive welfare. Overall, it can be said that the tendency towards different values and the feeling of subjective welfare is different among generations, but this difference is not that big to be named a "gap".